The impact of risk management on internal and sustainable growth rate: Evidence from Tehran Stock Exchange - Hamid Reza Vakili Fard; Ali Alizadeh; Karim Ghalmagh (Management Science Letters)
Measuring the relative risk of firms has been an open discussion among researchers. There are many studies on learning how leverage may influence on growth of the firms. This article reviews the relationship between risk management, internal and sustainable growth of accepted companies in Tehran stock exchange. The survey considers three types of risks including operating, financial and compound and investigates their relationships with internal growth rate as well as sustainable growth rate. Using some regression techniques, the study has determined negative and meaningful relationships between different types of leverage on side and internal as well as sustainable growth on the other side.